Ab Initio Flight Training: A Systematic Literature Review. Issue 2 (3rd April 2023) - Marques, Elvira; Carim, Guido; Campbell, Chris; Lohmann, Gui
ABSTRACT: Objective: This article aims to explore the literature on ab initio flight training from 1990 to 2020 and to identify main trends and gaps. Background: The literature about ab initio pilot training encompasses a variety of topics, traditions and publications. Characterizing what has been produced will identify themes and gaps in the literature to further advance the field. Method: A systematic literature review was conducted in which 75 studies, reviews and conceptual works were analyzed to ascertain the status of the literature on ab initio flight training. Results: Findings included topical research on subjects such as the use of technological resources to enhance flight training, such as Personal Computer-Based Aviation Training Devices (PCATDs), simulators, eye-tracking devices, and augmented and virtual reality (VR). These assistive technologies strengthen students' learning and create opportunities to reduce the time and cost of flight training. Another common finding among the reviewed references is the call to change the instructional methods and the curriculum. Other areas identified focus on student performance, including how to predict and assess it, and how it is influenced by human factors. Conclusion: A lack of guidance by instructors and flight schools was identified regarding the integration of technological resources, especially simulators, into the training curricula and what instructional methods are needed to enhance learning.